2022
DOI: 10.3389/fimmu.2022.1001025
|View full text |Cite
|
Sign up to set email alerts
|

From bench to bedside: Calprotectin (S100A8/S100A9) as a biomarker in rheumatoid arthritis

Abstract: S100A9/S100A8 (calprotectin), a member of the S100 protein family, has been shown to play a pivotal role in innate immunity activation. Calprotectin plays a critical role in the pathogenesis of rheumatoid arthritis (RA), as it triggers chemotaxis, phagocyte migration and modulation of neutrophils and macrophages. Higher calprotectin levels have been found in synovial fluid, plasma, and serum from RA patients. Recent studies have demonstrated better correlations between serum or plasma calprotectin and composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 151 publications
(61 reference statements)
0
32
0
3
Order By: Relevance
“…CX3CR1 [666], CD177 [690], PF4 [691], FFAR2 [692], MPO (myeloperoxidase) [693], F11 [694], S100A8 [695], VEGFD (vascular endothelial growth factor D) [674], IL1A [696], BPI (bactericidal permeability increasing protein) [697], AQP4 [698], BDNF (brain derived neurotrophic factor) [699], CXCL10 [700], RNASE2 [701], FCGR3B [702], S100A9 [703], IL1B [704], CXCR2 [705], GPIHBP1 [294], CD36 [706], TRIB3 [707], PCSK9 [708], FGF2 [709], FASN (fatty acid synthase) [710], PNPLA3 [711], HSPA6 [712], VIP (vasoactive intestinal peptide) [713], TLR3 [683], ADRB1 [328], SPOCK2 [714], TLR8 [715], CCR2 [716], IFIT3 [717], NEK7 [718], TLR7 [687], EFNB2 [719], CAV1 [720], CR1 [721] and AQP5 [722] plays essential roles in viral respiratory diseases. Previous study confirmed that CX3CR1 [723], S100A12 [724], CD177 [725], PF4 [726], MPO (myeloperoxidase) [727], CD5L [728], F11 [729], S100A8 [730], PGLYRP1 [731], GPR15 [732], BPI (bactericidal permeability increasing protein) [733], AQP4 [734], BDNF (brain derived neurotrophic factor) [735], CXCL10 [736], FCGR3B [737], S100A9 [738], IL1B [739], CXCR1 [740], CXCR2 [741], AFF3 [742], WNT3A [743], FCN3 [744], AZGP1 [745], CD36 [746], PCSK9 [747], GPX3 [748], FGF2 [749], SHH (sonic hedgehog signaling molecule) [750], SLC7A11 [751], VIP (vasoactive intestinal peptide) [752], KL (klotho) [753], APOA1 [754], RASGRF1 [75...…”
Section: Discussionmentioning
confidence: 69%
“…CX3CR1 [666], CD177 [690], PF4 [691], FFAR2 [692], MPO (myeloperoxidase) [693], F11 [694], S100A8 [695], VEGFD (vascular endothelial growth factor D) [674], IL1A [696], BPI (bactericidal permeability increasing protein) [697], AQP4 [698], BDNF (brain derived neurotrophic factor) [699], CXCL10 [700], RNASE2 [701], FCGR3B [702], S100A9 [703], IL1B [704], CXCR2 [705], GPIHBP1 [294], CD36 [706], TRIB3 [707], PCSK9 [708], FGF2 [709], FASN (fatty acid synthase) [710], PNPLA3 [711], HSPA6 [712], VIP (vasoactive intestinal peptide) [713], TLR3 [683], ADRB1 [328], SPOCK2 [714], TLR8 [715], CCR2 [716], IFIT3 [717], NEK7 [718], TLR7 [687], EFNB2 [719], CAV1 [720], CR1 [721] and AQP5 [722] plays essential roles in viral respiratory diseases. Previous study confirmed that CX3CR1 [723], S100A12 [724], CD177 [725], PF4 [726], MPO (myeloperoxidase) [727], CD5L [728], F11 [729], S100A8 [730], PGLYRP1 [731], GPR15 [732], BPI (bactericidal permeability increasing protein) [733], AQP4 [734], BDNF (brain derived neurotrophic factor) [735], CXCL10 [736], FCGR3B [737], S100A9 [738], IL1B [739], CXCR1 [740], CXCR2 [741], AFF3 [742], WNT3A [743], FCN3 [744], AZGP1 [745], CD36 [746], PCSK9 [747], GPX3 [748], FGF2 [749], SHH (sonic hedgehog signaling molecule) [750], SLC7A11 [751], VIP (vasoactive intestinal peptide) [752], KL (klotho) [753], APOA1 [754], RASGRF1 [75...…”
Section: Discussionmentioning
confidence: 69%
“…The present study has found that RAGE exhibits variable influence on DAMP release. S100A8/A9 is a heterodimeric DAMP, released from cells in response to stress or during cell death, with neutrophils being the primary source ( 79 ). Extracellular S100A8/A9 has strong antimicrobial activity and promotes local inflammation through binding of RAGE and TLR4 ( 80 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both S100A9 and S100A12 can regulate immune response and in ammation by inducing production of pro-in ammatory cytokines for neutrophil, monocyte and lymphocyte recruitment [30]. It was reported that S100A9 and S100A12 were signi cantly up-regulated and played an important role in pathogenesis of many in ammatory disease, such as rheumatoid, atherosclerosis and in ammatory bowel disease [31][32][33][34][35]. Although it still hasn't been widely applied in clinical diagnosis, the serum levels of S100A8/9 and S100A12 have already been proposed being potential biomarker for sJIA [7,36].…”
Section: Discussionmentioning
confidence: 99%